ANALISIS PENGARUH KEPUASAN SERVICE QUALITY DAN PERCEIPT PRICE TERHADAP KEPUTUSAN REPURCHASE INTENTION KONSUMEN : (Studi Kasus pada Konsumen Kafe Kopi Janji Jiwa) - Wahyu Setiyaningrum Beru, Tarigan; Haryo, Panji (Jurnal Pariwisata Indonesia, 2023)
This study aims to analyze how consumers decision to repurchase with variables or decisions made because of the quality of service, perceived price and satisfaction received by it. The data used in this research is to use primary data. With the total respondents being 202 informants. The application of the data source is by maximizing AMOS software for futher data processing. The results showed that there was a relationship between the variables determined so that it was positively related to the repurchase decision of the consumers. Positive customer satisfaction value of service and price perception offered, there is also a relationship between repurchase decision with service quality, price perception and customer satisfaction..